'Down with communism – Power to the people': The legacies of 1989 and beyond. (September 2020) - Ray, Larry; Stoyanova, Veronika
This special issue brings together reflections on the thirtieth anniversary of the revolutions of 1989 and considers their consequences for our understandings of European and global society. What seemed for some at least the surprising and rapid collapse of Eastern European state socialism prompted rethinking in social theory about the potential for emancipatory politics and new modes of social and political organization. At the same time, there was increased reflection on the nature of varieties of capitalism and the meaning of socialism beyond the failure of at least its etatist and autarkic mode. The five articles here and the editors' introduction address themes such as utopian hopes, civil society, the transformation of Europe, the world beyond 1989, and new configurations of power and conflict.